A Longitudinal Person‐Centered Examination of Affinity for Aloneness Among Children and Adolescents. Issue 6 (29th July 2020) - Daly, Owen; Willoughby, Teena
Abstract : Affinity for aloneness among youth often is viewed negatively. However, some youth may enjoy solitude for positive reasons, rather than because of social anxiety. The prevalence and adjustment over time of youth with high affinity for aloneness is unclear. Groups of children ( N = 605, M age = 9.29) and adolescents ( N = 596, M age = 12.20) were identified using affinity for aloneness and social anxiety scores, and group differences in adjustment were assessed. Latent class analyses revealed four groups at T1 and T2 for both samples. Among these were Normative (Low.affinity_for_aloneness‐Low.social_anxiety) and Affinity for Aloneness (High.affinity_for_aloneness‐LowMod.social_anxiety) groups. These groups did not differ longitudinally in adjustment. Having elevated levels of affinity for aloneness without high social anxiety is relatively benign.